Diosgenin Exerts Antitumor Activity via Downregulation of Skp2 in Breast Cancer Cells - Liu, Yanling; Zhou, Zijun; Yan, Jingzhe; Wu, Xuefeng; Xu, Guiying (BioMed research international, 2020)
Background. Breast cancer is the common malignancy with high morbidity and mortality in women. S-phase kinase-associated protein 2 (Skp2) has been characterized to play an oncogenic role in the breast carcinogenesis and progression. Therefore, inactivation of Skp2 in breast cancer might be a novel approach for fighting breast malignancy. A natural compound diosgenin has been reported to exert anticancer activity in a variety of human cancers. However, the underlying mechanism has not been fully determined. Methods. In this study, we aim to explore whether diosgenin performed antitumor activity via inhibition of Skp2 in breast cancer cells using several methods including MTT, Transwell invasion assay, RT-PCR, western blotting, and transfection. Results. We found that diosgenin inhibited cell viability and stimulated apoptosis. Moreover, we found that diosgenin reduced cell invasion in breast cancer cells. Furthermore, diosgenin inhibited the expression of Skp2 in breast cancer cells. Notably, diosgenin reduced cell viability and motility and induced apoptosis via suppression of Skp2 in breast cancer cells. Conclusion. Our findings revealed that diosgenin could be a potential inhibitor of Skp2 for treating breast cancer.